The Role of Muhammadiyah in Education in Indonesia - Kurniawati, Luthfiyah; Junaidi, Junaidi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Muhammad Darwis or better known as K.H. Ahmad Dahlan was the founder of Muhammadiyah on 8 Dzulhijjah 1330 Hijriah, coinciding with 18 November 1912, in the Kauman village of Yogyakarta. This research uses a qualitative approach to explore visual objects in the study area which, according to the views of local residents, have certain signs or symbols. Meanwhile, in the preparation the author used a type of research in the form of field research, with the aim of finding out real and specific phenomena that occur in society. In order for the data that the author describes to be academically accountable, a certain method is needed in conducting research. The results of the research explain that Muhammadiyah continues to increase its role and expand its work in improving and advancing Islamic education in Indonesia from time to time. A very real result is the creation of charitable efforts consisting of thousands of schools ranging from kindergartens to universities, hospitals, maternity centers, orphanages, nursing homes, social homes and economic institutions. With its educational potential, Muhammadiyah has made a very significant contribution to the development of national education in an effort to make the nation's life more intelligent. Muhammadiyah's educational contribution is quite proportional when compared to all privately managed education.